2003
DOI: 10.1161/01.str.0000063404.27912.5b
|View full text |Cite
|
Sign up to set email alerts
|

Opening of Mitochondrial ATP-Sensitive Potassium Channels Is a Trigger of 3-Nitropropionic Acid–Induced Tolerance to Transient Focal Cerebral Ischemia in Rats

Abstract: Background and Purpose-The role of mitochondrial ATP-sensitive potassium channels (mitoK ATP ) in ischemic tolerance has been well documented in heart, but little work has been done in brain. To investigate the involvement of mitoK ATP activation in chemical preconditioning in brain, we examined the effect of 5-hydroxydecanoate (5-HD), a selective mitoK ATP blocker, on neurotoxin 3-nitropropionic acid (3-NPA)-induced ischemic tolerance to transient focal cerebral ischemia in rats. Methods-Male Wistar rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 33 publications
1
47
0
Order By: Relevance
“…This approach has already been demonstrated to be beneficial in case of 3-NP: the low-dose of toxin treatment increased the tolerance to ischemia and hypoxia in rats and gerbils (Horiguchi et al, 2003;Riepe et al, 1997;Wiegand et al, 1999). Although the exact mechanism in the background is not fully understood, the overexpression of free radical scavenging enzymes may be involved: acute 3-NP treatment activated superoxide dismutase (SOD) and catalase (CAT) in several brain areas (Binienda et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This approach has already been demonstrated to be beneficial in case of 3-NP: the low-dose of toxin treatment increased the tolerance to ischemia and hypoxia in rats and gerbils (Horiguchi et al, 2003;Riepe et al, 1997;Wiegand et al, 1999). Although the exact mechanism in the background is not fully understood, the overexpression of free radical scavenging enzymes may be involved: acute 3-NP treatment activated superoxide dismutase (SOD) and catalase (CAT) in several brain areas (Binienda et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in heart 67 and brain 68 have suggested that enhanced tolerance to ischemia conferred by the SDH inhibitor 3-nitropriopionic acid might involve mitoK ATP opening, as evidenced by attenuation of the protection by 5-HD. Recent experiments suggest that 3-nitropriopionic acid activates mitoK ATP channels reconstituted from a highly purified mitochondrial membrane preparation, 69 and this effect was inhibited by 5-HD or glibenclamide, implying that SDH modulates mitoK ATP as part of a macromolecular complex.…”
Section: Inconsistencies In the Mitochondrial K Atp Channel Story Nonmentioning
confidence: 99%
“…To test this possibility, we pretreated transfected HEK293 cells with the mitoK ATP channel inhibitor 5-HD (100 M) for at least 15 min, followed by cell-attached patch recordings of Kir6.2/SUR1 channels before and during application of zaprinast (50 M) in the continuous presence of 5-HD (100 M). 5-HD, a natural lipid component of human milk, has been shown to disrupt ischemic tolerance conferred by ischemic and pharmacological preconditioning in heart and brain, which action is thought to result from inhibition of mitoK ATP channels (31,49). We found that zaprinast did not induce an increase in the single-channel activity of Kir6.2/SUR1 channels when 5-HD was coapplied (Fig.…”
Section: Zaprinast Stimulated Kir62/sur1 Channels In Intact Hek293 Cmentioning
confidence: 99%